Application of HYDRUS (2D/3D) for Predicting the Influence of Subsurface Drainage on Soil Water Dynamics in a Rainfed‐Canola Cropping System†. (6th December 2017) - Karandish, Fatemeh; Darzi‐Naftchali, Abdullah; Šimůnek, Jiří
Abstract: The HYDRUS (2D/3D) model was applied to investigate the probable effects of different subsurface drainage systems on the soil water dynamics under a rainfed‐canola cropping system in paddy fields. Field experiments were conducted during two rainfed‐canola growing seasons on the subsurface‐drained paddy fields of the Sari Agricultural Sciences and Natural Resources University, Mazandaran Province, northern Iran. A drainage pilot consisting of subsurface drainage systems with different drain depths and spacings was designed. Canola was cultivated as the second crop after the rice harvest. Measurements of the groundwater table depth and drain discharge were taken during the growing seasons. The performance of the HYDRUS‐2D model during the calibration and validation phases was evaluated using the model efficiency (EF), root mean square error (RMSE), normalized root mean square error (NRMSE) and mean bias error (MBE) measures. Based on the criteria indices (MBE = 0.01–0.17 cm, RMSE = 0.05–1.02 and EF = 0.84–0.96 for drainage fluxes, and MBE = 0.01–0.63, RMSE = 0.34–5.54 and EF = 0.89–0.99 for groundwater table depths), the model was capable of predicting drainage fluxes as well as groundwater table depths. The simulation results demonstrated that HYDRUS (2D/3D) is a powerful tool for proposing optimal scenario to achieve sustainable shallow aquifers in subsurface‐drained paddy fields during winter cropping. Copyright © 2017 John Wiley & Sons, Ltd.